AR gene rearrangement analysis in liquid biopsies reveals heterogeneity in lethal prostate cancer. Issue 9 (11th August 2021) - Daniel, Mark; Knutson, Todd P; Sperger, Jamie M; Li, Yingming; Singh, Anupama; Stahlfeld, Charlotte N; Passow, Courtney; Auch, Benjamin; Lang, Joshua M; Dehm, Scott M
Abstract : Castration-resistant prostate cancer (CRPC) is driven by AR gene aberrations that arise during androgen receptor (AR)-targeted therapy. AR amplification and mutations have been profiled in circulating tumor cells (CTCs), but whether AR gene rearrangements can be assessed in CTCs is unknown. In this study, we leveraged CRPC cell lines with defined AR gene rearrangements to develop and validate a CTC DNA analysis approach that utilized whole genome amplification and targeted DNA-sequencing of AR and other genes important in CRPC. We tested the utility of this approach by analyzing matched CTC DNA and plasma cell-free DNA (cfDNA) from a case series of ten CRPC patients. One of ten CTC samples and two of ten cfDNA samples were positive for AR gene rearrangements. All AR gene rearrangements were discordant between matched liquid biopsy samples. One patient harbored separate AR gene rearrangements in CTC DNA and cfDNA, but concordant AR amplification and AR T878A mutation. This patient also displayed concordant loss of TP53 and PTEN, but the loss of RB1 in cfDNA only. The overall frequency of discordant alterations in these genes between matched CTC DNA and cfDNA was high. This study establishes the technical feasibility of analyzing structural rearrangements, mutations, and copy number variants in AR and other CRPC genes using two different sources of DNA from a single blood sample. Paired CTC DNA and cfDNA analysis may have utility for capturing the heterogeneity of genetic alterations in CRPC patients.